Design, implementation and evaluation of virtual routing fowarding / Amaleena Basri - Basri, Amaleena (2011)
A network-based virtual network architecture by using fundamental routing mechanism is proposed. This mechanism is a virtual overlay network based, involving a number of sites as well as tunnels connectivity spanning to those sites. The technology employs a single router intents and purposes, but allowing multiple instances of a routing table to exist in a router and work simultaneously. A method is studied that enables a creation of single virtual system containing components spread across multiple locations. Virtual systems have become a popular as a result of the flexibility and cost savings. This method can be deployed in the current network with little investment and it is easy to implement. The simulation results show its performance is better than the current environment. The simulations are performed using GNS3 simulator.